Determinants of mother to child HIV transmission (HIV MTCT); a case control study in governmental health centers of East Gojjam Zone, Northwest Ethiopia, 2019 - Mengistie Kassahun Tariku (BMC, 2022)
Plain English summary Prevention of Mother to child human immune virus (HIV) transmission is the primary method of infection among children. To eliminate infection in children and keep mothers alive, a comprehensive package of interventions accelerating, including preventing of women from becoming infected with HIV, protect unwanted pregnancy, throughout pregnancy, provide skilled delivery, exclusive breastfeeding and providing appropriate HIV treatment, care, and support for mother and infants. Despite the availability and scale-up of life-saving interventions, only a few pregnant women living with HIV in Ethiopia have been receiving the medication to prevent mother to child HIV transmission. There is limited information about determinant of mother to child HIV transmission in Ethiopia. In this study, the data were extracted from the document of health centers ART register book, ANC follow up register book, PMTCT service registration log book charts and infant DBS tally sheets in East Gojjam, Ethiopia. This study revealed that high proportion of HIV infection among exposed infants in the study area. Infections with HIV among HIV exposed infants were positively associated with history of ANC follow up of their mothers and initial CD4 counts of their mothers.